Effect of Plant Growth-Promoting Rhizobacteria (PGPR) Application on Helminthosporium turcicum Infection and the Growth of Sweet Corn (Zea mays saccharata Surt.) - Putri, Rosy Cahyagung Dewi Basuki; Abadi, Abdul Latief (Journal of Tropical Plant Protection, 2026)
The study aimed to determine the effect of application Plant Growth-Promoting Rhizobacteria (PGPR). The research was carried out in the greenhouse dan laboratory of plant disease at the Brawijaya University Malang. The study was arranged in a Randomized Block Design which consisted of 8 treatments and 3 replications. The results showed that the single isolate treatment have the highest average incubation period of Helminthosporium turcicum, namely the single isolate of Bacillus subtilis and Pseudomonas fluorescens bacteria for 9 day. The treatment of the consortium of 3 bacteria, namely Bacillus subtilis+Pseudomonas fluorescens +UB19 (Pseudomonas sp). showed an excellent antagonistic activity in suppressing diseases caused by the fungus Helminthospororium turcicum. Pseudomonas sp. had the ability to increase the plants fresh weight but had no effect on the roots fresh weight.  However, the bacterial consortium (B. subtilis, P. fluorescens, and UB 19 (Pseudomonas sp.)) in sweet corn plant growth was indicated by the higher average yield of plant height, number and weight of roots compared to other treatments.